Pembuktian Kepemilikan Citra Digital dengan Teknik Steganografi menggunakan Matlab - Veronica Lusiana (Jurnal Ilmiah Dinamika Teknik, 2008)
Steganography is the art of hiding information in ways that prevent the detection of hiding messages. Digital technology gives us new ways to apply steganographic techniques, including hiding information in digital images. Steganography encompasses methods of trammitting secret messages through innocuous cover carries in such a manner that the very existence of the embedded messages is undetectable. The purpose ofsteganography is not to keep others from knowing the hidden information, but it is to keep others from thinking that the information even exists. If a s!eganography method causes someone to suspect the carrier medium. then the method has failed. Digital watermarking is described as a possibilüy to interface and close the gap between copyright and digital distribution. It is based on steganographic techniques and enables useful rights protection mechanisms.